2021
DOI: 10.3389/fgene.2021.769690
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of CircRNA Expression Profiles and Potential Functions in Brown Adipogenesis

Abstract: Brown adipose tissue (BAT) is specialized for energy expenditure, thus a better understanding of the regulators influencing BAT development could provide novel strategies to defense obesity. Many protein-coding genes, miRNAs, and lncRNAs have been investigated in BAT development, however, the expression patterns and functions of circRNA in brown adipogenesis have not been reported yet. This study determined the circRNA expression profiles across brown adipogenesis (proliferation, early differentiated, and full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“… 28 Li et al reported that circScd1 overexpression promotes steatosis in non-alcoholic fatty liver. 29 Previous reports also showed that circRNAs are abundantly expressed in BAT and WAT of mice, 22 , 23 however, there is no clear report on circRNA expression profiles in human BAT and WAT. So, here we aimed to explore the DECs between BAT and WAT, and attempted to identify some novel biomarkers for metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 Li et al reported that circScd1 overexpression promotes steatosis in non-alcoholic fatty liver. 29 Previous reports also showed that circRNAs are abundantly expressed in BAT and WAT of mice, 22 , 23 however, there is no clear report on circRNA expression profiles in human BAT and WAT. So, here we aimed to explore the DECs between BAT and WAT, and attempted to identify some novel biomarkers for metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“… 14–16 Numerous studies indicated that circRNAs play a critical role in the development of various diseases. 17–21 Recent reports indicate that circRNAs are differentially expressed in mice BAT and WAT, 22 , 23 but the pattern of differentially expressed circRNAs in human BAT and WAT remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study identified circRNAs profiles in white and brown AT, which provided circRNA candidates for regulating adipose formation. 186,187 Studies suggested that circ-SAMD4A increased preadipocyte differentiation, 188 and circArhgap5-2 played an essential role in adipogenesis and lipid metabolism. 189 Evidence suggests that downregulated hsa_circ_000839 in patients with BC exhibits a negative correlation with BMI, but the underlying mechanism is still unclear.…”
Section: Circrnas In Obesity-associated Diseasesmentioning
confidence: 99%
“…On the contrary, circARF3 (ADP‐ribosylation factor 3) could also strengthen mitophagy to subdue adipose inflammation by combining miRNA‐103., 185 but whether changes in this inflammatory state affect tumor development have not been confirmed. A recent study identified circRNAs profiles in white and brown AT, which provided circRNA candidates for regulating adipose formation 186,187 . Studies suggested that circSAMD4A increased preadipocyte differentiation, 188 and circArhgap5‐2 played an essential role in adipogenesis and lipid metabolism 189 …”
Section: Ncrnas In Obesity‐associated Diseasesmentioning
confidence: 99%
“… 10 In addition, two other studies explored the mouse white and brown adipogenesis, respectively. 11 , 12 Furthermore, some studies assessed the differentially expressed circRNAs (DECs) of VATs in human obese compare to lean individuals and VATs compare to subcutaneous adipose tissue (SATs). 8 , 13 In other animals, for instance, the circRNAs expression of Yak and Pig of SATs adipogenesis were also evaluated.…”
Section: Introductionmentioning
confidence: 99%